Islamic Religion through Islamic Montessori Learning: A Curriculum Development for Early Childhood - Windiastuti, Endah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to describe the inculcation of Islamic religious values for early childhood through the Montessori method. The method initiated by Maria Montessori, Italy has its own challenges due to the different years and places. This research was conducted in a kindergarten with an Islamic Montessori curriculum in Yogyakarta. The method in this research is qualitative analysis with data sources from observation and in-depth interviews with informants. The results of this study indicate that the cultivation of Islamic religious values is carried out in the Montessori learning process. The learning curriculum indirectly contributes to the model of inculcating Islamic values. The form of Islamic religious values is instilled with habituation, collaborative lectures with fun activities for children, and in the provision of teaching materials and food served to children. This method was successfully implemented in kindergarten with the expected results. In addition, Montessori learning does not experience difficulties and is very easy to use to apply Islamic religious values even though they are initiated from different places and distances.